A review on ice detection technology and ice elimination technology for wind turbine. Issue 3 (23rd December 2019) - Wei, Kexiang; Yang, Yue; Zuo, Hongyan; Zhong, Dingqing
Abstract: Blade icing can affect wind turbines to generate electricity. In severe cases, 30% of power generation is lost in a year, and safety problems in the vicinity of wind power plants are also caused. Researchers have designed anti‐icing and de‐icing technologies to reduce these effects, and excellent ice‐detecting devices are a prerequisite for using anti‐icing and de‐icing technologies. Ultrasonic attenuation technology can effectively and reliably detect the presence of ice without affecting the aerodynamic performance of the blade, providing a reliable guarantee for anti‐icing and de‐icing systems. Deicing and anti‐icing systems are divided into active and passive, active heating blades are still the most effective anti‐icing and de‐icing methods, but their energy consumption is too high. Although there are many existing de‐icing methods, there are not many practical uses. This article introduces them separately and lists their advantages and disadvantages. The use of ultrasonic anti‐icing and de‐icing is an economical and reliable means that has been proven to be used for anti‐icing and de‐icing of blades. However, under normal circumstances, a single anti‐icing de‐icing system cannot completely solve the problem of icing of the blades. This paper suggests using both ultrasonic and hydrophobic coatings to cope with more icing conditions.